A Qualitative Study of Patients' Experiences, Enablers and Barriers of Rheumatic Heart Disease Care in Uganda. Issue 1 (23rd February 2023) - Nalubwama, Hadija; Pulle, Jafesi; Atala, Jenifer; Sarnacki, Rachel; Nakitto, Miriam; Namara, Rebecca; Beaton, Andrea; Kansiime, Rosemary; Mwima, Rachel; Ndagire, Emma; Okello, Emmy; Watkins, David
Introduction: Rheumatic heart disease (RHD) remains a significant public health problem in countries with limited health resources. People living with RHD face numerous social challenges and have difficulty navigating ill-equipped health systems. This study sought to understand the impact of RHD on PLWRHD and their households and families in Uganda. Methods: In this qualitative study, we conducted in-depth interviews with 36 people living with RHD sampled purposively from Uganda's national RHD research registry, stratifying the sample by geography and severity of disease. Our interview guides and data analysis used a combination of inductive and deductive methods, with the latter informed by the socio-ecological model. We ran thematic content analysis to identify codes that were then collapsed into themes. Coding was done independently by three analysts, who compared their results and iteratively updated the codebook. Results: The inductive portion of our analysis, which focused on the patient experience, revealed a significant impact of RHD on work and school. Participants often lived in fear of the future, faced limited childbirth choices, experienced domestic conflict, and suffered stigmatization and low self-esteem. The deductive portion of our analysis focused on barriers and enablers to care. Major barriers included the high out-of-pocket cost of medicines and travel to health facilities, as well as poor access to RHD diagnostics and medications. Major enablers included family and social support, financial support within the community, and good relationships with health workers, though this varied considerably by location. Conclusion: Despite several personal and community factors that support resilience, PLWRHD in Uganda experience a range of negative physical, emotional, and social consequences from their condition. Greater investment is needed in primary healthcare systems to support decentralized, patient-centered care for RHD. Implementing evidence-based interventions that prevent RHD at district level could greatly reduce the scale of human suffering. There is need to increase investment in primary prevention and tackling social determinants, to reduce the incidence of RHD in communities where the condition remains endemic.